TREATMENT OF CANINE TOOTH EDGE TO EDGE MALRELATION AND INDIVIDUAL DENTAL MALPOSITION WITH REMOVABLE ORTHODONTIC DEVICE: CASE REPORT - Beta Arnanda, Bramita; Nurhayati (Fakultas Kedokteran Gigi Unjani, 2025)
Edge to edge is a malocclusion characterized by the upper teeth experiencing premature contact with the lower teeth. Treatment to improve anterior edge to edge is by retroclination of lower jaw teeth that experience initial contact or premature contact so that they fit into the normal mandibular arch. Case report: A 26 year old male patient came to RSGM FKG UMS with complaints of crowding in the front teeth of the lower jaw. This treatment is carried out using a removable orthodontic appliance which consists of an active component in the form of a labial arch with the aim of correcting edge-to-edge malrelation and a simple spring with the aim of correcting individual tooth malposition. As a result of 2 months of treatment, the anterior edge-to-edge was corrected, malposition of individual teeth was corrected and the appearance improved. Conclusion: Removable orthodontic treatment using a labial arch in cases of edge-to-edge malrelation of canines over 8 meetings gave quite good results. Appropriate case selection and patient compliance are necessary to achieve successful removable orthodontic treatment. DOI : 10.54052/jhds.v4n3.p313-324